The controls on the composition of biodegraded oils in the deep subsurface – Part 4. Destruction and production of high molecular weight non-hydrocarbon species and destruction of aromatic hydrocarbons during progressive in-reservoir biodegradation. (December 2017) - Oldenburg, Thomas B.P.; Jones, Martin; Huang, Haiping; Bennett, Barry; Shafiee, Nor Shahida; Head, Ian; Larter, Steve R.
Highlights: Destruction and production of compounds occurs during in-reservoir biodegradation. Oxidation of species impact transport, interfacial and corrosion properties of oils. Oil species with MW at least up to m/z 600 (C# 44) are affected by biodegradation. Biodegradation resistant, parameter set was developed for biodegraded case studies. Nitrogen-containing oil compounds are nitrogen and carbon source for microorganisms. Abstract: This study extends the analysis of previously well studied biodegraded crude oil case history sample sets. The analytical window is extended into the high molecular weight, aromatic hydrocarbon and non-hydrocarbon fraction of crude oils, using a 12 T ultra-high resolution mass spectrometer (FTICR-MS). Biodegradation is pervasive across compound groups and extent of degradation appears dependent on compound abundance and hence availability. Oil constituents with molecular weights up to m/z 600 (carbon number 44) are affected by in-reservoir biodegradation. Apart from special, specific compound groups possibly related to the active reservoir biomass, all hydrocarbon and single heteroatom-containing compound classes are depleted by biodegradation. Production of various highly alkylated species indicate that transformation of crude oil components often involves derivatization and preservation rather than just complete destruction of high molecular weight compounds. Whereas one case study shows good correlation between depletion of S1 species and a strong increase in SO2 species, a nitrogen enriched oil suite shows an analogous trend in the transformation of N1 species to the corresponding NO2 species. Increase in O2 species are seen in both sample sets indicating partial oxidation is a major overall process in in-situ reservoir biodegradation. These variations are important geochemically but also impact transport, interfacial and corrosion properties of oils. Nitrogen isotope systematics indicate that nitrogen-containing compounds might act as nitrogen nutrient sources or mainly as carbon sources for the microorganisms causing in-situ reservoir biodegradation depending level of biodegradation. Distributions of some heterocyclic species add a very biodegradation resistant parameter set, to the petroleum geochemists arsenal.